PENGARUH MODEL PEMBELAJARAN KOOPERATIF TIPE JIGSAW TERHADAP HASIL BELAJAR IPS SISWA KELAS V SDN 163 PEKANBARU - Elsi Gusmaini; Hendri Marhadi; Mahmud Alpusari (Jurnal Educhild : Pendidikan dan Sosial, 2022)
The purpose of this study in general is to obtain information about the effect of the Jigsaw type cooperative learning model on social studies learning outcomes for fifth grade students of SD Negeri 163 Pekanbaru. The method used in this research is the experimental method. The form of experimental research used is a quasi-experimental design with the type of Nonequivalent Control Group Design. The sample in this study was 70 students consisting of 35 students in class VB and 35 students in VC class. Based on the results of data analysis, the average post-test results of students were 83,71. From the test analysis results obtained sig (2-tailed) of 0,000  0.05, where Ha is accepted and  is rejected. Then, based on the results of the calculation of how much influence the Jigsaw type cooperative learning model has on the social studies learning outcomes of class V students, the coefficient of determination R Square (R2) was tested which obtained 64,6% results and the remaining 35,4% was influenced by other factors. Which were not investigated in this study. So it can be concluded that there is a significant effect of the use of the Jigsaw Cooperative Learning Model on the social studies learning outcomes of fifth graders at SD Negeri 163 Pekanbaru. Tujuan penelitian ini secara umum untuk mendapatkan informasi mengenai pengaruh model pembelajaran kooperatif tipe Jigsaw terhadap hasil belajar IPS siswa kelas V SD Negeri 163 Pekanbaru. Metode yang digunakan dalam penelitian ini adalah metode eksperimen. Bentuk penelitian eksperimen yang digunakan adalah desain quasi eksperimen dengan jenis Nonequivalent Control Group Design. Sampel dalam penelitian ini adalah sebanyak 70 siswa yang terdiri dari siswa kelas VB yang berjumlah 35 orang dan siswa kelas VC yang berjumlah 35 orang. Berdasarkan hasil analisis data diperoleh hasil rata-rata post-test peserta didik 83,71. Dari hasil analisis uji-t diperoleh sig (2-tailed) sebesar 0,000  0.05, dimana Ha diterima dan  ditolak. Kemudian, berdasarkan hasil perhitungan seberapa besar pengaruh model pembelajaran kooperatif tipe Jigsaw terhadap hasil belajar IPS siswa kelas V, dilakukan uji koefisien determinasi R Square (R2) yang memperoleh hasil sebesar 64,6% dan sisanya 35,4% dipengaruhi oleh faktor-faktor lain yang tidak diteliti dalam penelitian ini. Jadi dapat disimpulkan bahwa terdapat pengaruh yang signifikan penggunaan Model Pembelajaran Kooperatif Tipe Jigsaw terhadap hasil belajar siswa kelas V SD Negeri 163 Pekanbaru.